Development of an Electronic Module Based on the PQ4R Strategy to Enhance Students Critical Thinking Skills - Jeklin Hutagaol; Nurul Kholiza Priani; Riska Herlena. S (Jurnal Media dan Teknologi Pendidikan, 2026)
Low critical thinking skills among students, particularly on the human nervous system material, have become a significant issue in biology learning because this topic requires high-level analysis, evaluation, and problem solving abilities. This study aims to develop, test, and analyze the feasibility of an electronic module based on the Preview, Question, Read, Reflect, Recite, Review (PQ4R) strategy that is valid, practical, and effective in enhancing students’ critical thinking skills. This research employed a Research and Development approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The study subjects were eleventh grade students. Data were collected using critical thinking tests, interview sheets, expert validation questionnaires for media and material, and student practicality questionnaires. Data were analyzed using descriptive quantitative analysis and ANOVA to test the module’s effectiveness. The results indicated that the developed electronic module met the criteria for validity according to expert assessment, was practical based on student responses, and was effective in improving students’ critical thinking skills. Students who used the PQ4R based electronic module demonstrated higher improvement in critical thinking compared to students who received conventional learning. The study concludes that the PQ4R based electronic module is a feasible digital learning innovation to support independent learning and strengthen students’ critical thinking skills. The implication of this study is that the PQ4R based electronic module can be used as a flexible learning alternative, promoting active student engagement and enhancing learning effectiveness outside the classroom.